2021
DOI: 10.1117/1.ap.3.5.055001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced generation of nondegenerate photon pairs in nonlinear metasurfaces

Abstract: We predict theoretically a regime of photon-pair generation driven by the interplay of multiple bound states in the continuum resonances in nonlinear metasurfaces. This nondegenerate photon-pair generation is derived from the hyperbolic topology of the transverse phase matching and can enable orders-of-magnitude enhancement of the photon rate and spectral brightness, as compared to the degenerate regime. We show through comprehensive simulations that the entanglement of the photon pairs can be tuned by varying… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 38 publications
1
53
0
Order By: Relevance
“…Finally, and most interestingly, when substituting η SPDC in equation ( 3), we estimate a photon pair generation rate, normalized to the pump power, of 1.75 kHz mW −1 . This magnitude is similar to the prediction for BIC-enhanced in a 2D metasurface that emits in the normal direction [23], whereas the 1D metasurface considered in this work allows for a broad off-normal angular emission that may be desirable for different types of applications. We note that the aperture angle of signal or idler photon emission is relatively narrow, being about 8 • , centred at 23 • emission angle (i.e.…”
Section: Enhanced Photon-pair Generationsupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, and most interestingly, when substituting η SPDC in equation ( 3), we estimate a photon pair generation rate, normalized to the pump power, of 1.75 kHz mW −1 . This magnitude is similar to the prediction for BIC-enhanced in a 2D metasurface that emits in the normal direction [23], whereas the 1D metasurface considered in this work allows for a broad off-normal angular emission that may be desirable for different types of applications. We note that the aperture angle of signal or idler photon emission is relatively narrow, being about 8 • , centred at 23 • emission angle (i.e.…”
Section: Enhanced Photon-pair Generationsupporting
confidence: 82%
“…Notably, the strongest enhancement of nonlinear interactions in metasurfaces can be achieved through resonances based on bound states in the continuum (BICs) [20][21][22]. It was recently suggested theoretically that BICs in metasurfaces composed of reduced-symmetry nanoresonators can be used to enhance the photon-pair generation rate and spectral brightness [23]. However, the photon emission was predicted to occur primarily in the close to normal direction.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelength-dependent complex refractive index of Si is extracted from experimental data 49 , and the constant refractive index of 1.45 is assigned to SiO 2 . Note that we choose the dimer design as it belongs to a symmetric geometry of C 2v group and possesses more structural parameters to be tuned than C 4v configurations [50][51][52][53][54][55][56][57][58][59] . Benefiting from the additional degree of freedom, it is possible to manipulate the excitation of dual BIC resonances by adjusting the structural geometry and rotating the fundamental pump polarization.…”
Section: Polarization-controlled Dual Bound States In the Continuummentioning
confidence: 99%
“…S1). We then use the CMT to efficiently simulate the sum frequency generation (SFG) process and calculate the SPDC emission via quantum-classical correspondence [17,19]. Figure 1d shows the predicted photon-pair rate integrated over their frequency spectra vs. the transverse momenta in the metasurface plane, for a normally incident plane-wave pump with the frequency ω p = 2×191.19 THz.…”
Section: Concept and Modellingmentioning
confidence: 99%
“…An enhancement of SPDC through localized Mie-type optical resonances [16] in nanoantennas [17] and metasurfaces [18] was experimentally demonstrated. Recent theoretical studies [19][20][21] suggested that using metasurfaces with nonlocal lattice resonances can further boost the SPDC efficiency, yet the realization of this concept remained outstanding.…”
Section: Introductionmentioning
confidence: 99%